Circulating Immune Cell Profile and Changes in Intravenous Immunoglobulin Responsiveness Over the Disease Course in Children With Kawasaki Disease - Choi, In Su; Lee, Mi Ji; Choi, Seul A.; Choi, Kyung Soon; Jeong, In Seok; Cho, Hwa Jin (Frontiers in Pediatrics, 2022)
Kawasaki disease (KD) is an acute, self-limited febrile illness of young children. The etiology of KD remains to be poorly understood. There has been limited research on longitudinal examination of peripheral blood leukocytes for immune profiling particularly in relation to treatment response with intravenous immunoglobulin (IVIG). This study profiles immune cells at the time of diagnosis and over the disease course. In addition, we identified the characteristics of the immune cells in IVIG-responsive patients with KD. We enrolled patients diagnosed with KD between May 1, 2017 and January 1, 2020. Blood was taken at least three times from all enrolled patients: at diagnosis (before IVIG infusion), and immediately and 2 weeks after IVIG infusion. We evaluated the laboratory findings and results of flow cytometry analysis of immune cells at all stages, focusing on CD4+ T lymphocytes, CD8+ T lymphocytes, CD19+ B lymphocytes, granulocytes, classical monocytes, and natural killer (NK) cells. Non-febrile healthy controls (NFC) and other febrile controls (OFC) were also enrolled. A total of 68 patients were enrolled and divided into two groups according to IVIG resistance status: IVIG-responsive (n = 55) and IVIG-resistant (n = 13). The total fever duration was significantly longer in the IVIG-resistant group (9.7 ± 5.3 days) than in the IVIG-responsive group (6.7 ± 3.0 days; P = 0.02). There was a significant difference in intermediate CD14+CD16+ monocytes between KD patients and both NFC and OFC; they were significantly higher and lower in KD patients than NFC and OFC, respectively (P < 0.001). The levels of all three subtypes of NK cells were significantly lower in KD patients than in both NFC and OFC (P < 0.001). Regarding IVIG responsiveness, CD14+CD16+ intermediate monocyte levels were significantly lower in the IVIG-resistant group (P < 0.001). In addition, CD56-CD16+ NK cell expression was significantly lower in the IVIG-resistant than IVIG-responsive group (P = 0.002). In conclusion, our results suggest CD56-CD16+NK cells and CD14+CD16+ intermediate monocytes might play an essential role in immunopathogenesis of KD. Further studies are warranted to explore the role of these subpopulations particularly for the observed association to CAL and treatment response.